Clinical estimation of fundamental frequency: The 3m plastiform magnetic tape viewer - Kelly, Dan H; Sansone, Frank (Journal of Communication Disorders, 1981)
A procedure and method is described to determine the frequency or pitch of tape-recorded voice samples, while keeping the cost of measurement within the reach of practicing clinicians. The method described reduces the uncertainty of pitch determination by comparison techniques and improves the accuracy of clinical estimation of fundamental vocal frequency and pitch. The accuracy, reliability, cost, and ease with which the method can be used makes it a viable tool to be used by the clinician. © 1981.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/065-059-031-584-761 tex.type: [object Object]
Keywords: Human; Methods; Pitch Perception; Tape Recording; Voice Disorders; article; dept.cmd; hearing; human; instrumentation; larynx disorder; tape recorder; technique